The Effect Of Communication And Work Ethic On Work Performance With Competence As An Intervening Variable At The Bank Indonesia Representative Office In North Sumatra Province - Raja Pardomuan H. Siregar; Mesra B (Yayasan Multidimensi Kreatif, 2024)
This research aims to be the final project of the graduation requirements in obtaining a S2 degree, and another purpose of this research is to be used as an input for organizations to develop even better, Everyone is unique in their needs, desires, interests, values, beliefs, attitudes, mental processes, perceptions, and personalities, among others (Umam, 2012). An organization or corporation is established on the basis of a vision for the benefit of humans, and it is humans who regulate the implementation of the mission of the organization or company Human interaction begins with communication. Humans can interact with each other through communication in a variety of environments, including markets, workplaces, homes, and public spaces. No one in this world would shy away from participating in his talks. The results of this study are as follows: Work Ethic has a positive and significant effect on Competence with the original sample value of 0.652 p values 0.000. Work Ethic had a positive and significant effect on Work Achievement with the original sample value of 0.429 and p values of 0.002. Competence had a positive and significant effect on Work Achievement with an original sample value of 0.419 and p values of 0.000. Communication had a positive and significant effect on Competency with the original sample value of 0.243 and p values of 0.014. Communication had a positive and insignificant effect on Work Performance with the original sample value of 0.090 and p values of 0.228. Work Ethic has a positive and significant effect on Work Achievement through Competency indirectly with the original sample value of 0.273 and p values of 0.001. Communication has a positive and significant effect on Work Achievement through Competence with the original sample value of 0.102 and p values of 0.044.